Perbandingan Metode Fuzzy Time Series Markov Chain dan Fuzzy Time Series Chen Average Based untuk Peramalan Volume Impor Migas. - Agan; Teti Sofia Yanti (UNISBA Press, 2022)
Abstract. Forecasting is the process of estimate about something happening in the future based on empirical data, while a time series is an analysis that considers the influence of time in order. This research discusses forecasting using two Time Series methods, namely Fuzzy Time Series Markov Chain and Fuzzy Time Series Chen Average Based. These two methods are developments of the Fuzzy Time Series using the basic fuzzy principle first introduced by Prof. Lotfi A Zadeh, then developed by Song and Chissom. These two methods are developments of the Fuzzy Time Series using the basic fuzzy principle first introduced by Prof. Lotfi A Zadeh, then developed by Song and Chissom. Forecasting using the Fuzzy Time Series is a technique that captures data patterns from the past and then used to project or predict the future by looking at fuzzy relationships or relationships formed by determining logical relationships from data involving fuzzy relationships from each partition of the universal set. In this research, we will compare the FTS Markov Chain and FTS Chen Average Based methods by looking at the results of the Mean Absolute Percentage Error (MAPE) calculation to measure which method has the best accuracy in the volume of oil and gas imports. The results of mape calculations obtained the Fuzzy Time Series Markov Chain method more accurately in translating the volume of oil and gas imports in Indonesia for 2022. Abstrak. Peramalan adalah proses perkiraan tentang sesuatu yang terjadi pada waktu yang akan datang berdasarkan data empiris, sedangkan times series adalah analisis yang mempertimbangkan pengaruh waktu secara berurutan. Penelitian ini membahas mengenai peramalan dengan menggunakan dua metode Time Series yaitu Fuzzy Time Series Markov Chain dan Fuzzy Time Series Chen Average Based. Dua metode tersebut merupakan hasil pengembangan dari Fuzzy Time Series menggunakan prinsip fuzzy dasar yang pertama kali diperkenalkan oleh Prof. Lofti A Zadeh, kemudian dikembangkan oleh Song dan Chissom. Peramalan menggunakan Fuzzy Time Series merupakan teknik yang menangkap pola data dari masa lalu kemudian digunakan untuk memproyeksikan atau meramal masa depan dengan melihat dari relasi atau hubungan fuzzy yang dibentuk dengan menentukan hubungan logika dari data yang melibatkan hubungan fuzzy dari tiap partisi himpunan universal. Pada penelitian ini akan membandingkan anatara metode FTS Markov Chain dan FTS Chen Average Based dengan meilhat hasil perhitungan Mean Absolute Percentage Error (MAPE) untuk mengukur metode mana yang memiliki akurasi terbaik dalam volume impor migas. Hasil dari perhitungan MAPE diperoleh metode Fuzzy Time Series Markov Chain lebih akurat dalam meramalkan nilai volume impor minyak dan gas tahun 2022.